Post traumatic stress disorder and co-morbid psychological disorders after Palestinians’ home demolition: a comparative study - Sarhan, Adnan Lutfi; Jarrar, Kamal; Atout, Sameeha; Masri, Walaa (Frontiers in Psychiatry, 2024)
Home demolition is one of the issues that the Palestinian community faces as a result of Israeli procedures that can impact Palestinian mental health. This study aimed to measure the prevalence of Post-Traumatic Stress Disorder (PTSD), depression, anxiety, and stress among Palestinian citizens whose homes were demolished. A comparative cross-sectional design was adopted using a purposive sample of home demolished versus not home demolished Palestinian people. The Impact of Event Scale-Revised (IES-R) and the Depression and Anxiety Stress Scales (DASS) were used to assess the participants' levels of PTSD, depression, anxiety, and stress. The Statistical Package for the Social Sciences, Version 25, was applied to the statistical analysis. This study showed that PTSD levels among people whose homes were demolished are significantly high, with a mean of 3.2, which could be indicative of a clinical concern. However, the PTSD level in the comparison group had no significance, with a mean of 1.48. Stress, depression, and anxiety levels were represented as 32.71, in their means, 32.61, and 32.08, respectively, among home-demolished people, compared to stress 18.46, depression 15.87, and anxiety 13.06 among the non home demolished group. This study is one of the few that sheds light on one of the disadvantaged groups who suffer from home demolition and the severe mental problems that affect them, including PTSD, stress, depression, and anxiety). Furthermore, many related risk factors were studied in this research. As a future recommendation, further research is needed in this field, especially among disadvantaged groups. Stakeholders need to take action to improve the health system in Palestine.